THE ROLE OF THE FAMILY IN FORMING NATIONALISM - Rudy Gunawan (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2018)
The background of this writing is the decreasing of nationalism among the youth of the nation. Nowadays, the nationalism seems to be sunk. Nowadays, it is facing a great challenge to civilization, named globalization. As the basic drive and the élan vital, the flexibility of Indonesia nationalism is being tested in terms of the ability to change, so it is hoped that it is always accurate in answering the occurring-demand. The flexibility is not decreasing the nationalism; it is, in fact, shows the deep of nationalism itself so at the same time it is still alive and continuously metamorphosed.The aim of this writing is to investigate the role of the family in the nationalism, both individually and together among the youth. This research conducted in the analytical description method. The discussion shows that the family environment has a role in growing the nationalism. It is also shown that the family has a great role in forming the nationalism among the youth. It is concluded that the education in the family gives a good impact toward the nationalism among the youth. Parents who educate their children to love their nation by asking them to follow the national events in their childhood will help the children to love their nation and country.